A Survey on Energy Hole in Clustering Routing Protocol of Wireless Sensor Networks - Odeyinka, Oluwadara J; Ndinechi, Michael C; Nosiri, Onyebuchi C; Onuekwusi, Nnaemeka C (Journal of Asian Scientific Research, 2020)
Wireless Sensor Networks (WSNs) has become an active branch in the field of Communication Engineering. Owing to energy demand of wireless sensor nodes and the entire network structure, different routing protocol had been developed to address the constraint on sensor nodes battery. Clustering Routing Protocol (CRP) being the most effective approach used could suffer a major drawback as nodes close to the Sink depletes their energy first, thereby resulting into energy hole whereby data routed to the Sink through the affected nodes become interrupted. This paper takes a sample of wireless sensor networks on selected perimeters and the possibility of energy hole on the sampled networks using a single and different hierarchical level metrics simulated in Matlab environment. The result revealed that nodes far away from the Sink still retain a large joules (J) of Energy above the mean energy residue values even though the structured network had failed. Hence, possible solutions to alleviate the challenges posed due to energy hole in similar networks are recommended.